Terpenes: Multifunctional roles for plant survival and sustainable farming - Sakthi, K J; Sritharan, N; Djanaguiraman, M; Senthil, K G; Marimuthu, S (Plant Science Today, 2025)
Terpenes are the largest class of plant secondary metabolites which play a major role in plant-environmental interactions and serve vital ecological and agricultural functions. Their volatile nature plays a crucial role in pollination and insect attraction by emitting chemical signals that lure pollinators and seed dispersers, while simultaneously repelling herbivores and attracting the predators of the pests. Terpenes exhibit strong antimicrobial and antiviral activities, making them highly effective against pathogens. The insecticidal activity of terpenes offers an effective and eco-friendly alternative to synthetic pesticides, helping to kill pests in an environmentally sustainable manner. Allelopathic interactions of terpenes suppress the germination and growth of weeds and offer sustainable weed management. Besides, terpene biosynthesis in plants is influenced by abiotic stresses such as drought, elevated temperature, light stress and UV radiation highlighting the critical role in defense and adaptation mechanisms in relation to environmental changes. β-caryophyllene, a sesquiterpene is crucial for pollination, pest management, pathogen resistance, allelopathy and stress tolerance, enhancing survival and sustainability of plants. Modulation of terpene levels due to climate change emphasize their role in improving plant resilience to changing environments. The involvement of terpenes in diverse biotic and abiotic interactions underscores the need for continued research to harness their sustainable applications in agriculture, ecology and beyond.